Technology Advancement, Teachers’ Efforts and Know - How as Key factors to Improve Students’ Creativity for Excellence in Education Management - Nath, Archana; Behura, Ajit Kumar; Kumar, Ritesh; Kanak, Tara; Sundararajan, Muniyan (Prabandhan: Indian Journal of Management, 2019)
Through this paper, we have made an attempt to prove how innovation in teaching could be effectively used in attaining better understanding of the subjects, promoting academic excellence, and enhancing quality among the students. The present paper suggested innovative teaching as the need of the present age of globalization and examined in brief how such innovation in teaching could make learning more interesting and enjoyable. This paper further compared the traditional method of teaching with the modern methods, where technology has taken the front seat. This article further explored an innovative pedagogical method incorporating the teaching resources of the present age as per the students’ creativity that naturally differ from person to person, though the living environment is the same. Further, we attempted to explain the quality of different teaching methods, deriving an appropriate mathematical model and compared it hypothetically with the proposed innovative method which incorporated the effect of the students’ creativity as well.